1986
DOI: 10.1295/polymj.18.741
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Dependence on the Morphological Properties of Polyethylene Gels

Abstract: ABSTRACT:Polyethylene gels were prepared by gelation/crystallization from dilute decalin solutions using five kinds of polyethylenes with different molecular weights and degrees of branching. The decalin was allowed to evaporate from the gels under ambient condition in order to prepare dry gels. The dry gel of ultra-high molecular weight polyethylene (UHMWP) of M w = 6 x 10 6 forms a film but the other low molecular weight polyethylenes (LMWP) with molecular weight lower than 3 x I 0 5 do not form a film. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 35 publications
2
56
0
Order By: Relevance
“…Sawatari et al [14] showed that for ultra-high molecular weight polyethylene gel films the optimal concentration, i.e. the concentration at which just enough realized at this concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sawatari et al [14] showed that for ultra-high molecular weight polyethylene gel films the optimal concentration, i.e. the concentration at which just enough realized at this concentration.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some entanglements are necessary to warrant sufficient coherence of the starting structure to allow drawing without premature breakage [12,13]. For this reason there is an optimal concentration [14].…”
Section: Introductionmentioning
confidence: 99%
“…17 • 18 As for low molecular weight polyethylene, the dried gel cannot form a film and within the film there exist spherulitic textures. 19 Judging from the relationship between the morphology of the superstructure and molecular weight for polyethylene dry gels, it may be postulated that the existence of rodlike textures within dry gel polypropylene films is also due to the ultra-high molecular weight used in the present work.…”
mentioning
confidence: 86%
“…The key element in obtaining high-strength UHMWPE fibers is to find a way to draw the as-prepared gel specimens to an ultrahigh draw ratio after the gel spinning process. The drawability of the as-prepared gel specimens was found to depend significantly on the compositions of solutions from which gels were made [12][13][14][15][16][17]. Several authors [16,[18][19][20][21][22] reported that the drawing temperature and rate could markedly affect the maximal achievable draw ratio and tensile properties of solution-grown UHMWPE samples.…”
Section: Introductionmentioning
confidence: 99%